Oneweb: web content adaptation platform based on w3c mobile web initiative guidelines (2011)
Restrictions regardingnavigability and user-friendliness are the main challenges the Mobile Web faces to be accepted worldwide. W3C has recently developed the Mobile Web Initiative (MWI), a set of directives for the suitable design and presentation of mobile Web interfaces. This article presents the main features and functional modules of OneWeb, an MWI-based Web content adaptation platform developed by Mobile Devices Applications Development Interest Group’s  (W@PColombia) research activities, forming part of the Universidad de Cauca’s Telematics Engineering Group.Some performance measurementresults and comparison with other Web content adaptation platforms are presented. Tests have shown suitable response times for Mobile Web environments; MWI guidelines were applied to over twenty Web pages selected for testing purposes.